Editorial: Honesty in Marketing - Belanger, G.M. (Canadian Journal of Optometry, 1989)
In recent months, this writer's office has been bombarded with promotional literature from firms in the ophthalmic community offering gifts and prizes for the purchase of specific items, whether they be spectacle frames/lenses, contact lenses or contact lens solutions. We are not here alluding to the usual volume discounts on orders, but rather to prizes and gifts offered in exchange for what actually amount to relatively small purchases.